Investigations on the Chemical Compositions and Biological Efficiencies of Some Public Health Pesticide Formulations under Different Storage Conditions* - YAVUZ, OGUZHAN (Asian Journal of Chemistry, 2010)
Seven public health insecticide formulations were stored at 4, 21ºC with 50-55 % relative humidity and 31ºC with 60-70% relative humidity in 1 L coex bottle during 12 months. The formulations contained two synthetic pyrethroids (deltamethrin and permethrin) and two organophosphates (chlorpyrifos-ethyl and chlorpyrifos-methyl) active ingredients. Changes of active ingredients were determined by gas chromatography equipped with flame ionization detector at intervals of 3 months. Biological efficacy of insecticides on house fly (Musca domestica L.) were investigated at intervals of 3 months and the residual efficiency of the insecticides which were applied to surface floor tiles were measured at intervals of 15 ± 3 d during 12 months. In spite of unacceptable changes of active ingredients in certain times, the biological efficacy test results of formulations stored in the original package showed that death and knock down effect percentages were above the effectiveness level (70%) in all conditions during 12 months. Although knock down effect percentages of all formulations, which were applied on surface floor tiles, were very low in the end of the study. Biological efficiency was determined longer than expected. Knock down effect of the synthetic pyrethroid formulations were determined longer than organophosphates. No statistical significance was determined between storage conditions (p > 0.05).